Missed opportunities in full immunization coverage: findings from low- and lower-middle-income countries - María Clara Restrepo-Méndez; Aluísio J. D. Barros; Kerry L. M. Wong; Hope L. Johnson; George Pariyo; Fernando C. Wehrmeister; Cesar G. Victora (Global Health Action, 2016)
Background: An estimated 23 million infants are still not being benefitted from routine immunization services. We assessed how many children failed to be fully immunized even though they or their mothers were in contact with health services to receive other interventions. Design: Fourteen countries with Demographic and Health Surveys and Multiple Indicator Cluster Surveys carried out after 2000 and with coverage for DPT (Diphtheria-tetanus-pertussis) vaccine below 70% were selected. We defined full immunization coverage (FIC) as having received one dose of BCG (bacille Calmette-Guérin), one dose of measles, three doses of polio, and three doses of DPT vaccines. We tabulated FIC against: antenatal care (ANC), skilled birth attendance (SBA), postnatal care for the mother (PNC), vitamin A supplementation (VitA) for the child, and sleeping under an insecticide-treated bed-net (ITN). Missed opportunities were defined as the percentage of children who failed to be fully immunized among those receiving one or more other interventions. Results: Children who received other health interventions were also more likely to be fully immunized. In nearly all countries, FIC was lowest among children born to mothers who failed to attend ANC, and highest when the mother had four or more ANC visits Côte d'Ivoire presented the largest difference in FIC: 54 percentage points (pp) between having four or more ANC visits and lack of ANC. SBA was also related with higher FIC. For instance, the coverage in children without SBA was 36 pp lower than for those with SBA in Nigeria. The largest absolute difference on FIC in relation to PNC was observed for Ethiopia: 31 pp between those without and with PNC. FIC was also positively related with having received VitA. The largest absolute difference was observed in DR Congo: 41 pp. The differences in FIC among whether or not children slept under ITN were much smaller than for other interventions. Haiti presented the largest absolute difference: 16 pp. Conclusions: Our results show the need to develop and implement strategies to vaccinate all children who contact health services in order to receive other interventions.